Powerful oscillation damping controller for VSC renewable generators using hydrogen energy storage systems; International Journal of Hydrogen Energy; Vol. 60 - Ufa R. A. Ruslan Alexandrovich; Rudnik V. E. Vladimir Evgenevich; Malkova Ya. Yu. Yana Yurievna; Tomalev A. A. Andrey Aleksandrovich; Sarsikeyev Y. Z.; Zhantlessova A. B. (2024, 2024)
Title screen